Introduction to the archaeological study in the Ocros province, Ancash (Ocros, Santiago de Chilcas and Acas districts) - van Dalen Luna, Pieter D. (2014)
Ocros Province is one of the largest in the department of Ancash, in the ten districts presenting more than 500 archaeological sites of dierent periods, unfortunately so far not been investigated. e Study Group Ñawpaq Qastiquna department of Archaeology of San Marcos has begun work on archaeological survey in the province of Ocros, identifying a total of 45 archaeological sites of which 80% of the data is presented.